ANALISIS PERAN REGULATOR DAN ASPEK BIAYA DALAM PENCEGAHAN PRAKTIK PREDATORY PRICING DI ECOMMERCE INDONESIA - Biantara, Dheny; Margaretha, Viona; Lesmana, Iwan (School of Accountancy, University of Agung Podomoro, 2022)
This study analyzes the role of regulators in Indonesia and the cost aspects that can preventpredatory pricing in an E-Commerce. Cross-border sellers who are successful in offering lower pricesin Indonesian E-Commerce bring concerns and threats to local MSMEs. The government as theregulator decided to prohibit the import of 13 product categories in the E-Commerce marketplace toanticipate unhealthy business practices. This phenomenon is also known as predatory pricing. . Theparameters used in this study are product similarity, selling price and other information that can beused to support research analysis. Grouping product categories and confirming products is a way tounderstand the phenomena that occur in data taken from the Shopee E-Commerce marketplace whichfocuses on competition between domestic sellers where there are 13 products with